Understanding the Definition of Science, Philosophy and Religion - Ni'mah, Azkiyatun; Khasanah, Siti Marzukotul (Penerbit Hellow Pustaka, 2026)
In this universe, there are many phenomena and events that spark human curiosity in exploring them. Therefore, knowledge, philosophy, and religion are needed to understand these matters. This study aims to review the concepts and relationships of knowledge, philosophy, and religion in general. This research discusses the definition of knowledge, the definition of philosophy, the essence of religion, and the reciprocal relationship between knowledge, philosophy, and religion. The method used in this study is library research. The data collection technique used in this study involves literature review taken from sources related to the research focus. Data analysis in this study is divided into data reduction, data presentation, and drawing conclusions.